(untitled) (Research, Society and Development, 2022)
Pernambuco has a relevant part of the population that survives from family farming and a substantial portion of this contingent lives in very dry areas. In this scenario, Pronaf, emerges as an important instrument for the poorest groups, especially in the Northeast. In this perspective, the purpose of this article was to analyze how the resources of the Program were distributed among the municipalities of Pernambuco, considering the division of the territory into Development Regions (DR), in the period from 2013 to 2018. For this, we used indexes of Gini, T of Theil and Concentration, making it possible to understand to what extent the distribution of resources was correlated with the importance of these municipalities in state family farming, in terms of number of establishments, area, employed people and production value. As a result, it was found that costing contracts were more unequal and concentrated than investment contracts. As for the variables analyzed, it was observed that they did not reflect the relative importance of the municipalities in family farming and proved to be little dissonant, mainly in relation to the value of production (for funding), demonstrating a greater relationship between these indicators and the distribution of financing.